Dynamic behavior of stay cables with passive negative stiffness dampers. (24th June 2016) - Shi, Xiang; Zhu, Songye; Li, Jin-Yang; Spencer, Billie F
Abstract: This paper systematically investigates the dynamic behavior of stay cables with passive negative stiffness dampers (NSD) installed close to the cable end. A passive NSD is modeled as a combination of a negative stiffness spring and a viscous damper. Through both analytical and numerical approaches, parametric analysis of negative stiffness and viscous damping are conducted to systematically evaluate the vibration control performance of passive NSD on stay cables. Since negative stiffness is an unstable element, the boundary of passive negative stiffness for stay cables to maintain stability is also derived. Results reveal that the asymptotic approach is only applicable to passive dampers with positive or moderate negative stiffness, and loses its accuracy when a passive NSD possesses significant negative stiffness. It has been found that the performance of passive NSD can be much better than those of conventional viscous dampers. The superior control performance of passive NSD in cable vibration mitigation is validated through numerical simulations of a full-scale stay cable.